2007
DOI: 10.22495/cocv4i2p13
|View full text |Cite
|
Sign up to set email alerts
|

Corporate governance and bank performance: Does ownership matter? Evidence from the Kenyan banking sector

Abstract: This paper provides an empirical analysis of banks performance in Kenya. The primary purpose of this study is to investigate the association between ownership structure characteristics and bank performance. Data utilised in the study is collected from the Financial Institutions Department of the Central Bank of Kenya, both on-site inspection reports and off-site surveillance records. Empirical results indicate that ownership structure of banks significantly influence their financial performance. In particular,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
17
0
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(22 citation statements)
references
References 14 publications
3
17
0
2
Order By: Relevance
“…Table 3 shows the correlation matrix for the variables under investigation. The correlation that is worthy of note is the 0.667 correlation between MPS and EPS, which is however below the maximum correlation of 0.8 allowable (see Barako & Tower;2006;Gujarati & Sangeetha, 2007). The correlation analysis suggests that multicollinearity does not present a challenge in this study.…”
Section: Normality Testsmentioning
confidence: 58%
See 1 more Smart Citation
“…Table 3 shows the correlation matrix for the variables under investigation. The correlation that is worthy of note is the 0.667 correlation between MPS and EPS, which is however below the maximum correlation of 0.8 allowable (see Barako & Tower;2006;Gujarati & Sangeetha, 2007). The correlation analysis suggests that multicollinearity does not present a challenge in this study.…”
Section: Normality Testsmentioning
confidence: 58%
“…Second, we perform correlation analysis to establish the short-run relationship between the independent and control variables. It has been suggested that checks for multicollinearity among the explanatory variables generally are necessary because high correlations cause problems about the relative contribution of each predictor to the success of the model (Barako & Tower, 2006).…”
Section: Regression Modelsmentioning
confidence: 99%
“…The low correlation among the independent variables is an indication that multicollinearity may not be a problem to the study. The suggestion in the empirical literature is that correlation between the independent variables is considered undesirable for multivariate analysis only if it exceeds 0.8 (see Barako & Tower;Gujarati & Sangeetha, 2007).To further confirm the absence of multicollinearity among the independent variables, variance inflation factor (VIF) was used. The VIF for all the variables is less than 3 which is far less than 10 considered harmful for regression analysis (ibid).…”
Section: Resultsmentioning
confidence: 99%
“…Fallatah and Dickins (2012), concluded that corporate governance and firm performance (measured as return on assets) are unrelated, but corporate governance and value of firm (as measured by Tobin's Q and market value of equity) are positively related. Barako and Tower (2007), found foreign and government ownership in board are negatively related with firm performance. Similarly, Heracleous (2001) conducted a research on the theme and concluded, "researches have failed to find any convincing connection between the best practices in corporate governance and organizational performance".…”
Section: Literature Reviewmentioning
confidence: 99%